2001
DOI: 10.2135/cropsci2001.4151395x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Plant Pathogenicity of Endophytic Beauveria bassiana in Bt Transgenic and Non‐Transgenic Corn

Abstract: Field and greenhouse studies were conducted to determine the proclivity of Bacillus thuringiensis (Bt) (Berliner)‐transgenic corn (Zea mays L.) to form an endophytic relationship with Beauveria bassiana, and to evaluate the corn for possible plant pathological effects associated with this relationship. Beauveria bassiana (Balsamo) Vuillemin was applied as a granular formulation to two separate lines of corn, expressing Bt events MON802 and MON810, and their corresponding isolines. There were no significant dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 9 publications
1
22
0
2
Order By: Relevance
“…Plant growth in vermiculite was much less than in sterile and non-sterile soil, regardless of the inoculation method. Lewis et al (2001) reported no differences in growth between plants treated or not treated with B. bassiana. In the current study, seed treatment with B. bassiana did not reduce seed germination or seedling growth, and did not result in the development of root disease.…”
Section: Growth Medium Plant Parts Colonized (%)mentioning
confidence: 94%
“…Plant growth in vermiculite was much less than in sterile and non-sterile soil, regardless of the inoculation method. Lewis et al (2001) reported no differences in growth between plants treated or not treated with B. bassiana. In the current study, seed treatment with B. bassiana did not reduce seed germination or seedling growth, and did not result in the development of root disease.…”
Section: Growth Medium Plant Parts Colonized (%)mentioning
confidence: 94%
“…Nevertheless, in a subsequent paper Bing and Lewis (1992b) report surface-sterilization of tissues and recovery of B. bassiana, thus providing evidence of an endophytic relationship. The possible mode of action for endophytic B. bassiana against O. nubilalis was not discussed in any of these studies or in subsequent studies (Lewis et al, , 2001. The fact that no mycosed insects were reported (except for Bing and Lewis, 1993-see Section 4) suggests that the reduced tunneling reported in all the papers (Lewis and Cossentine, 1986;Lewis and Bing, 1991;Bing and Lewis, 1991;Bing and Lewis, 1992a,b;Lewis et al, 1996) could be a result of feeding deterrence or antibiosis.…”
Section: Introductionmentioning
confidence: 95%
“…Some entomopathogenic fungi, such as Beauveria bassiana (Bals. ), form a symbiotic relationship with plants and can subsequently infect insects that feed on these plants; B. bassiana appears to establish equally well in maize producing or lacking Cry toxins (Lewis et al, 2001). Taken together, these studies suggest that direct effects of GM crops on entomopathogens are either subtle or absent.…”
Section: Entomopathogensmentioning
confidence: 99%